Business Model Innovation in the Digital Ecosystem: The Role of Transformation, Readiness, and Digital Inclusion for Sustainable Economic Growth - Sunday Ade Sitorus; Nalom Siagian; Orlando Steven (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
The rapid acceleration of digital transformation has changed the business landscape worldwide, but micro, small, and medium enterprises (MSMEs) in developing regions continue to face structural gaps in digital readiness and inclusion. In Medan, Indonesia, where MSMEs are the backbone of the economy, limited digital adoption and uneven readiness hinder their ability to maintain competitiveness and contribute to inclusive economic growth. This phenomenon highlights the importance of analysing how digital transformation variables interact with innovation processes and collaborative ecosystems to generate sustainable economic outcomes. The objective of this study is to investigate the indirect effects of digital readiness, digital inclusion, and digital transformation on sustainable local economic development through the dual mediation of innovation business models and ecosystem business models. Using an explanatory quantitative design, data were collected from 200 SMEs in Medan that had been involved in digitalisation for at least two years. Structural Equation Modelling–Partial Least Squares (SEM-PLS) was applied to test the proposed Digital Ecosystem Innovation Model (DEIM). The results show that digital readiness, inclusion, and transformation do not have a direct effect on sustainable economic growth. Instead, their impact becomes significant when mediated by innovation and ecosystem business models. Digital readiness strongly drives innovation, while digital inclusion enhances both innovation and ecosystem collaboration. Furthermore, the ecosystem business model emerges as the strongest predictor of sustainable local economies, highlighting the importance of coordinated value creation among stakeholders. This study concludes that digital transformation should not be viewed as an end goal, but rather as a systemic process requiring business model adaptation and the development of collaborative ecosystems. This research contributes theoretically by expanding the Technology–Organisational Environment (TOE) framework through the DEIM model, integrating readiness, inclusion, and innovation into a holistic approach. Practically, this research provides policy insights to improve the resilience of MSMEs through digital literacy, innovation capacity, and cross-sector collaboration.